Identification of the first endogenous Ophiovirus sequence - Marsile-Medun, Soledad; Debat, Humberto Julio; Gifford, Robert James (BioRxiv, 2022)
Endogenous viral elements (EVEs) are sequences in eukaryotic genomes that are derived from the ancestral integration of viral sequences into germline cells. Ophioviruses (family Ophioviridae) are a recently established family of viruses that infects plants. In this report, we describe the first example of an EVE derived from an ophiovirus, in the genome of eelgrass (Zostera marina). These findings extend the host range of ophioviruses to include seagrasses of the family Zosteraceae, and provide a potential time calibration for the evolution of the Ophioviridae family.